Die Geschichte von der Fußwaschung (Joh 13) - Abramowski, Luise (Zeitschrift für Theologie und Kirche, 2005)
In this work, the author explores the relationship between John 6 and John 13. The foot washing is defined as Jesus' last legacy, meaning that it takes priority over baptism and the Eucharist. The narrative expresses the claim to a unique relationship with Jesus.